(untitled) (TEL Tempo, Espaço e Linguagem, 2026)
This article analyzes the musical training of adolescents who commit offenses at the Socio-Educational Care Center (CASE) in Goiânia, Goiás, between 2011 and 2022. It starts from the premise that detention, according to the ECA (Brazilian Statute of Children and Adolescents) and SINASE (National System of Socio-Educational Assistance), should articulate accountability and social emancipation. In this way, the Workshop for Musical Production and Expression emerges as a pedagogical space for the re-signification of youth experiences, favoring autonomy. Based on Paulo Freire’s critical pedagogy, the PNEDH (National Plan for Education in Human Rights) and the DNEDH (National Guidelines for Education in Human Rights), the study adopts action research with participant observation of musical compositions. The results indicate music as an instrument of emancipation, identity, resistance, and promotion of human rights in the socio-educational context.